HPV-Positive Oropharyngeal Cancer Via p16 Immunohistochemistry in Japan. (February 2017) - Toman, Julia; Von Larson, Scott; Umeno, Hirohito; Kurita, Takashi; Furusaka, Tohru; Hasegawa, Hisashi; Prasad, Manju L.; Sasaki, Clarence T.
Objectives: Human papillomavirus (HPV) has emerged as a driving cause of head and neck cancer, but investigations outside the West are limited. A p16 immunohistochemistry is a commonly used biomarker for HPV cancers. We sought to investigate the pathology and rates of HPV head and neck oropharyngeal cancer in Japan via p16 immunohistochemistry at 2 institutions in Japan. Methods: Fifty-nine oropharyngeal specimens from 2 university hospitals in Japan were examined for morphology and p16 immunohistochemistry. The rate of p16 positivity was then determined, and the 2 groups were compared for differences in age, smoking history, gender, and stage of presentation and mortality. Results: The rate of p16 positivity among the oropharyngeal specimens was 29.5%. There were important differences in the pathology compared to morphology usually seen in the US. The patients with p16+ cancer tended to be younger. There was no significant difference in smoking status. Patients with p16+ cancers trended toward better survival. Conclusion: There appears to be a geographical difference in HPV rates of oropharyngeal cancers with persistently lower rates in Asian countries when compared to Western Europe and the US. Conclusions about HPV head and neck squamous cell carcinoma (HNSCC) in Western countries may not be generalizable across the globe at this time.